ANIMAL-ASSISTED THERAPY: FOUNDATIONS, BENEFITS, AND APPLICATIONS IN MENTAL HEALTH - Muñoz, Cristian Fernan Muñoz; Domínguez, Laura Sofia Ramírez; Rodríguez, Felipe Lozano; Orrego, Orlando Posada (Seven Editora, 2026)
Animal-assisted therapy has gained increasing relevance in the field of mental health as a complementary intervention that integrates animals into therapeutic processes with the aim of promoting individuals’ psychological, emotional, and social well-being. The objective of this article is to analyze the conceptual foundations of animal-assisted therapy, the psychological benefits documented in the scientific literature, and its main applications in clinical, educational, and community contexts, with special attention to contributions developed in the Latin American context. The research was conducted through a systematic literature review following PRISMA methodology guidelines. The search for information was carried out in international academic databases such as Scopus, Web of Science, PubMed, SciELO, and Google Scholar. Keywords in Spanish and English related to animal-assisted therapy and human–animal interaction were used. Scientific articles published between 2010 and 2024 were included, as well as systematic reviews, meta-analyses, and empirical studies related to psychological, clinical, or educational applications. The thematic analysis of the literature allowed the identification of five main categories: theoretical foundations of human–animal interaction, psychological and physiological effects of animal-assisted therapy, therapeutic applications in mental health, interventions in educational and community contexts, and ethical considerations in the implementation of these programs. The reviewed studies show benefits associated with stress and anxiety reduction, mood improvement, strengthening of social skills, and increased emotional well-being across diverse populations. In conclusion, animal-assisted therapy constitutes an innovative therapeutic strategy that can complement traditional mental health interventions, although further empirical research in Latin American contexts is needed.